ANALISIS RASIO MODAL KERJA PADA KOPERASI UNIT DESA BAHAR SATRIA - Muhammad Bahar Saputra (Journal of Management and Social Sciences, 2023)
This study aims to determine the analysis of working capital ratios in the village unit cooperative bahar satria. The method used is a qualitative postpositivism approach. The object of this study is the ratio of working capital in the Bahar Satria village unit cooperative. Based on the results of the study, data was obtained that the working capital ratio at the Bahar Satria Village Unit Cooperative seen from 4 ratios is that the Current Ratio has fluctuated from 2018 – 2021. Then the Quick Ratio has fluctuated from 2018 – 2021. And the Cash Ratio has fluctuated from 2018 – 2021. Then the Inventory Ratio has fluctuated from 2018 – 2021. The standard ratio for the Working Capital Ratio in the Bahar Satria Village Unit Cooperative based on the Current Ratio can be said to be very good because it reaches 229.08%, then on the Quick Ratio it can be said to be good because it reaches 152 .99%, then the Cash Ratio can be said to be sufficient because it reaches 25.40%. And the ratio of Inventory to Net Working Capital can be said to be very good because it reaches 42.66%.